Epidemiology of thymic epithelial tumors: 22-years experience from a single-institution - Rioja, PJ (2021)
Background: To assess the correlation of WHO histological classification and Masaoka-Koga staging system of thymic epithelial tumors (TETs) with prognosis. Methods: We retrospectively analyzed 83 patients with TETs in the Instituto Nacional de Enfermedades Neoplasicas between 1996 to 2018. We analyzed the clinical stages, histological types and treatment modalities and attempted to determine the impact on overall survival. The data was retrieved from clinical files and reviewed by a pathologist who reclassificated according to the 2004 WHO classification system. The staging was performed with the Masaoka-Koga staging system. Survival curves were constructed with Kaplan-Meir method. Results: There was a total of 83 patients with a median age of 55 years old included in the study. The histological type corresponded to thymoma (T) in 63.8% (n = 53) and to thymic carcinoma (TC) in 36.1%. T were type A, AB, B1, B2 and B3 in 14.4%, 18%, 12%, 3.6%, 7.4% of cases, respectively. The proportion of advanced disease (Masaoka stage III-IV) was high (65%). With a median follow-up of 88.4 months, median overall survival (OS) was 81.6 months for T and 12.3 months for TC (P = 0.01). Univariate analysis showed that sex, histological type, clinical stage and surgery (P = 0.01) were significant independent prognostic factors. On multivariate analysis, histology type and Masaoka-Koga staging had an effect on survival. Conclusions: The results indicates a clear association between the WHO histological classification and Masaoka-Koga staging system with survival. We found a higher proportion of TETs with advanced disease at diagnosis. Further research are required and collaboration is important to foster knowledge focused on classification and treatment.